Molecular Exercise Physiology : an introduction - Wackerhage, Henning (Routledge, Taylor & Francis Group, 2014)
"'Molecular Exercise Physiology: An Introduction' is the first student-friendly textbook to be published on this key topic in contemporary sport and exercise science. It introduces sport and exercise genetics and the molecular mechanisms by which exercise causes adaptation and various related topics. The text is always linked to real life sport and exercise science situations such as 'what makes people good at distance running?', 'what DNA sequence variations code for a high muscle mass?' or 'by what mechanisms does exercise improve type2 diabetes?'"--